Neuroinflammation in white matter tracts of Cnp1 mutant mice amplified by a minor brain injury. Issue 6 (9th March 2013) - Wieser, Georg L.; Gerwig, Ulrike C.; Adamcio, Bartosz; Barrette, Benoit; Nave, Klaus‐Armin; Ehrenreich, Hannelore; Goebbels, Sandra
<x xml:space="preserve">Abstract</x> Oligodendrocytes make myelin for rapid impulse propagation and contribute to the long‐term survival of myelinated axons. The mechanisms by which oligodendroglial dysfunction(s) contribute to slowly progressive neurodegeneration are not well understood. Here, we demonstrate in Cnp1 mutant mice that secondary axonal degeneration in the subcortical white matter is associated with an age‐dependent activation of both, innate and adaptive immune responses, including an expansion of infiltrating CD8+ T cells. While the detrimental role of lymphocytes in inherited myelin diseases is known, the role of activated microglia for the hypothetical cycle of inflammation/degeneration is unclear. We used a mild standardized cryolesion of the right parietal cortex to activate microglia at the vulnerable age of mouse puberty (postnatal day (P) 28). When applied to Cnp1 mutant mice, analyzed more than 3 months later, minor brain injury had acted as a "second hit" and significantly enhanced astrogliosis, microgliosis and axon degeneration, but not T cell infiltration. Interestingly, exacerbated neuropathological changes were also reflected by specific deterioration of working memory on top of an essentially normal basic behavior. We propose a model in which oligodendroglial dysfunctions can trigger a vicious cycle of neurodegeneration and low‐grade inflammation that is amplified by nonspecific activators of the innate immune system. This interaction of genetic and environmental factors may be relevant for neuropsychiatric diseases associated with secondary neuroinflammation.